(3SfhGJ cGfJ YQHj (B/s - (3fhjgV,YGOd s ((3HjQhJ (B:s (3eDSSI fhjgV GdKbGajI ,s, 1990)
(3eLehYI bUUjI QGFYI cJHJ HCSdhH Sgd eeJY hTjb dJdGFe eOGQc fGTFJfG GdYQHjI h GdZSdGejI afchf NjQ Yhf dge aj eSjQJge fMh fMh GdeSJbHd JVe GdSdSdI bUU GdCfHjGA GdPjf CQSdge Gddg dgOGjI GdHTQ h JUa YXeI CYeGdge heG UGOage ef MhGOK eY CbhGege WjdI MjGJge GdRGNQI HdcaGM h GdLgGO(B.s
Keywords: (3SfhGJ s; (3YQHjs